Challenges and Opportunities of Micro-Scale Business Development by Housewives During Pandemic: Tantangan dan Peluang Pengembangan Bisnis Skala Mikro oleh Ibu Rumah Tangga di Kala Pandemi - Jum'ati, Nurleila; Lukmana, Ardiansyah Hendra; Azizah, Nur Aini; Wulandari , Siti; Rachmania, Rischa Ayu; Wulan, Dyah Puspita Indah Budi Sari (Universitas Muhammadiyah Sidoarjo, 2022)
MSME Tirtasari Raka Rayi, owned by a housewife, started a business in early 2020 that produces healthy drinks. The healthy drink produced are suitable for all ages by utilizing natural ingredients derived from agricultural products. They are called Sarkajo, Jeniper Mint, Sarkurma and Sargunies. During the Covid-19 pandemic, people's movements for outdoor activities is limited. It effects in a tremendous on all life aspects, including the economic activities of Tirtasari Raka Rayi MSMEs. In sales, the partner depends on incoming orders and still use offline or direct selling. On the other hand, the business legality is not owned by the partners. The method used by the community service team is personal assistance to partners who are housewives, such as product and marketing innovation and business legality. MSME Tirtasari Raka Rayi got the following results: 1) product innovations other than healthy drinks. It is frozen food: a) steamed and fried race chicken, b) gepuk beef, c) firecracker lungs; 2) online marketing of healthy drinks and frozen food products using social media: Whats Apps and Instagram; 3) business legality as an entrepreneur: Entrepreneurial Registration Number (NIB) and Small Medium Business License (IUMK). Based on the results obtained, it can be concluded that the pandemic period is an opportunity for partners who are housewives. The opportunity is to improve and develop the busess by adapting and innovating. Thus, the Covid 19 pandemic is a challenge and opportunity for MSME business development.